Perspective Woman Muslim to Program KB at Cipondoh Health Center - Sa'adah, Nur Hikmatu; Deviyanti, Luckyana; Herlina, Herlina; Al Maududi, Abul A'la (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2026)
ABSTRACT This study aims to determine Muslim women's perspectives on the implementation of the Family Planning (FP) program at the Cipondoh Community Health Center. The family planning program is one of the government's strategies to reduce population growth and improve the quality of family health and well-being. However, among Muslim women, there are still differing views on contraceptive use, influenced by religious, social, and cultural factors. This study used a descriptive method with a quantitative approach to describe the level of knowledge, attitudes, and acceptance of Muslim women towards the family planning program. The results showed that most Muslim women have a positive view of the family planning program because it is considered to align with the principles of family welfare and health. However, some respondents were still hesitant to participate in this program due to differing religious beliefs or limited information. Education, age, husband's support, and the role of health workers significantly influenced the acceptance of family planning among Muslim women. In conclusion, Muslim women's acceptance of the family planning program at the Cipondoh Community Health Center (Puskesmas) was quite good, but a more effective and sensitive approach to outreach to Islamic values ​was still needed. Collaboration between health workers, religious leaders, and the government was essential to increase public understanding that family planning is a family planning effort that aligns with Islamic teachings and plays a vital role in improving family health and well-being.